GANGRENA SECA EM FELINO NEONATO - Libardoni, Renato d. N.; Schossler, João E.; Serafini, Gabriele M. C.; Müller, Daniel C. d. M.; Silva, Marceli d.; Fritzen, Henrique S. (Salão do Conhecimento, 2013)
Resumo